A zinc-bromine liquid flow battery electrode material and preparation method thereof
By ultrasonic cleaning, drying, modifying and calcining the natural wood sheets, zinc-bromine flow battery electrode materials with high electrochemical activity were prepared, which solved the problem of slow kinetics of Br2/Br-redox reaction in zinc-bromine flow batteries, and significantly improved the overall performance of the battery.
Patent Information
- Application Number
- CN202411848160.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The slow kinetics of Br2/Br-oxidation reaction in zinc-bromide flow batteries lead to high electrochemical polarization and low battery power density, which hinders the commercialization and application of zinc-bromide flow batteries.
A zinc bromine liquid flow battery electrode material is used to prepare a zinc-brominated liquid flow battery electrode material, including ultrasonic cleaning, drying, modification and two calcining treatments to form an electrode material with excellent electrolyte wetting and electronic conductivity.
By improving the electrochemical activity of electrode materials, the overall performance of zinc-brominated flow batteries is improved. The average battery coulomb efficiency (CE) is as high as more than 94.7%, the voltage efficiency (VE) is as high as more than 84.1%, and the energy efficiency (EE) is as high as more than 79.7%.
Smart Images

Figure CN119340405B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery electrodes, and in particular relates to a zinc-bromine liquid flow battery electrode material and a preparation method thereof. Background Art
[0002] Large-scale energy storage technology can enhance the frequency and peak regulation capabilities of the power grid and is the key to achieving widespread use of renewable energy. Zinc-bromine flow batteries have attracted much attention for their advantages such as independent regulation of energy and power, high safety, long cycle life, and low cost. - The sluggish redox reaction kinetics is considered to be the main factor leading to the high electrochemical polarization and low battery power density of zinc-bromine flow batteries, which hinders the further commercialization and application of zinc-bromine flow batteries.
[0003] The electrode material is Br2 / Br - Redox provides a reaction site, and its performance has an important influence on the performance of zinc-bromine flow batteries. An ideal electrode needs to have excellent electrolyte wettability and electronic conductivity to provide sufficient active sites for bromine redox reactions. Carbon felt or graphite felt with a three-dimensional porous structure is widely used as an electrode for zinc-bromine flow batteries due to its large specific surface area, good electronic conductivity, and good chemical stability. However, due to the relatively poor hydrophilicity of carbon felt and graphite felt and the complex pore structure, the electrode-electrolyte interface resistance is high, resulting in low electrochemical activity. Summary of the invention
[0004] In order to solve the problems existing in the background technology, the present invention provides a zinc-bromine liquid flow battery electrode material and a preparation method thereof, which can effectively improve the electrochemical activity of the prepared electrode material, thereby improving the overall performance of the battery.
[0005] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a method for preparing an electrode material for a zinc-bromine flow battery, comprising the following steps:
[0006] S1. Cut the natural wood into pieces along the vertical growth direction with a thickness of 5-7 mm, then ultrasonically clean and dry the pieces with deionized water and ethanol to obtain clean wood chips;
[0007] S2, immersing the clean wood chips obtained in S1 in the modifier, heating to 40-45°C to promote the modifier to penetrate into the wood chips, keeping the temperature for 10-12 hours, taking out, drying, and obtaining the modified wood chips;
[0008] S3. The modified wood chips obtained in S2 are calcined in an argon atmosphere at 360-400° C. for 0.5-2 h, then calcined at 960-1000° C. for 2-3 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0009] Furthermore, the preparation method of the modifier is as follows:
[0010] A1. Dissolve 10 g of melamine-modified resin in 100-120 mL of ethanol solution to obtain a resin solution;
[0011] A2. Add 4-5g of boric acid to the resin solution obtained in A1, heat and stir to dissolve, and the modifier is obtained.
[0012] Furthermore, in A1, the mass fraction of the ethanol solution is 35-45%.
[0013] Furthermore, in A2, the specific operation of heating and stirring to dissolve is: heating to 45-50° C., stirring speed 150-180 r / min, stirring time 35-40 min.
[0014] Furthermore, the preparation method of the melamine modified resin is as follows:
[0015] B1. Add 94.11 g of phenol to a four-necked flask equipped with an electric stirrer, a thermometer and a serpentine condenser, and then add 33.3 g of a 30% NaOH solution, and stir at room temperature for 10 min.
[0016] B2, then add 60.06g of formaldehyde, react at 45℃ for 20min, slowly raise the temperature to 85℃, keep warm and continue to react for 30min;
[0017] B3. Then add 50.4-62.6g of melamine and 24-32g of formaldehyde, evenly raise the temperature to 90°C, keep warm for 2-3h, and finally cool to 45°C to obtain melamine-modified resin.
[0018] Furthermore, in S1, the natural wood is any one of basswood, beech, birch, oak, poplar and teak.
[0019] Furthermore, in S1, ultrasonic cleaning is performed with water for 6-8 hours, and then ultrasonic cleaning is performed with ethanol for 6-8 hours.
[0020] Furthermore, in S1, the drying temperature is 50-70°C, and the drying time is 12-15h.
[0021] Furthermore, in S2, the drying temperature is 50-70°C, and the drying time is 7-10h.
[0022] In a second aspect, the present invention provides a zinc-bromine liquid flow battery electrode material, which is prepared by the above-mentioned preparation method.
[0023] This application has the following beneficial effects:
[0024] 1. The present invention first uses a homemade modifier to soak the natural wood chips, and then calcines them twice at 360-400°C and 960-1000°C; natural wood itself is a biomass-based raw material, which is degradable, environmentally friendly, and significantly reduces production costs; by calcining and carbonizing the natural wood chips, the directional hierarchical through-hole structure of the wood itself can be retained, the electrolyte permeability can be improved, and the Br in the electrode can be shortened. - transport path, promoting mass diffusion to increase Br2 / Br - The reaction kinetics are improved and the battery polarization is reduced. The electrode material finally prepared is applied to zinc-bromine liquid flow batteries. The average coulombic efficiency (CE) of the battery is as high as over 94.7%, the voltage efficiency (VE) is as high as over 84.1%, and the energy efficiency (EE) is as high as over 79.7%, indicating that the electrode material prepared by the present invention has excellent electrochemical activity, can achieve efficient energy conversion and storage in the battery, and can ensure the excellent overall performance of the prepared battery.
[0025] 2. In the preparation of the modifier of the present invention, the nitrogen-containing compound melamine is first introduced into the (phenolic) resin to obtain the melamine-modified resin, and then the boron element (boric acid) is introduced into the melamine-modified resin to form a more stable three-dimensional network structure, improve the modification stability, and obtain the modifier;
[0026] The wood is immersed in the modifier, and the nitrogen-containing compound melamine is calcined at high temperature to dope the nitrogen element into the carbon skeleton of the wood, which can significantly improve its thermal oxidation stability; the boron element is added to the wood through a similar method, which can also improve the thermal oxidation stability of the wood; and the resin solution itself is impregnated into the wood, which can polymerize at high temperature to form a stable three-dimensional network structure, thereby enhancing the (channel structure / morphology / size) stability of the wood (after calcination), and then improving the electrochemical activity of the prepared electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 , a comparison trend chart of average coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE) test data of the electrodes prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 5 and applied in zinc-bromine liquid flow batteries;
[0028] Figure 2 , a comparison trend chart of test data of battery charge and discharge voltage difference (ΔV) at different current densities in zinc-bromine flow batteries using electrodes prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 5;
[0029] Figure 3 , surface morphology of the electrode obtained in Example 1 of the present invention;
[0030] Figure 4 , a partial enlarged view of the surface morphology of the electrode obtained in Example 1 of the present invention;
[0031] Figure 5 , surface morphology of the electrode obtained in comparative example 4 of the present invention. DETAILED DESCRIPTION
[0032] The present application is further described in detail below with reference to the embodiments.
[0033] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0034] Example 1: (1) Preparation of melamine modified resin, the preparation method is as follows:
[0035] B1. Add 94.11 g of phenol and 33.3 g of 30% NaOH solution into a four-necked flask equipped with an electric stirrer, a thermometer and a serpentine condenser. Continue stirring at room temperature at a speed of 220 r / min for 10 min.
[0036] In this step, phenol is first reacted with a 30% by mass NaOH solution at room temperature for 10 minutes. Phenol, as a weak acid, can react with the strong base NaOH to generate sodium phenol and water for the subsequent addition reaction of formaldehyde.
[0037] B2. Then add 60.06g of formaldehyde, react at 45°C for 20min, slowly raise the temperature to 85°C, and keep the temperature to continue reacting for 30min.
[0038] In this stage, in an alkaline environment, sodium phenolate will exchange protons with oxygen atoms in formaldehyde to generate a negatively charged formaldehyde anion and a positively charged phenol cation; the negatively charged formaldehyde anion will attack the hydrogen atoms at the ortho or para position of the phenol cation to generate an intermediate, namely hydroxymethylphenol; further condensation reactions will occur between multiple hydroxymethylphenols, removing water molecules and forming ether bonds. As the temperature gradually rises to 85°C, the condensation reaction continues to form a polymer (phenolic resin).
[0039] B3. Then add 55g of melamine and 28g of formaldehyde, evenly raise the temperature to 90°C, keep it warm for 2.5h, and finally cool it to 45°C to obtain melamine-modified resin.
[0040] In this stage, after adding melamine and additional formaldehyde, the system is evenly heated to 90°C and kept warm for 2-3 hours; melamine and formaldehyde undergo a condensation reaction to form a cross-linked network containing a triazine ring structure. At the same time, the previously generated polymer also participates in this cross-linking process, further strengthening the network structure of the resin. Finally, the reaction mixture is cooled to 45°C to obtain a melamine-modified resin, which not only reduces the temperature of the system, but also helps stabilize the structure of the resin and prevent further polymerization or degradation.
[0041] Among them, phenol was purchased from Shandong Jubang Chemical Co., Ltd. Melamine (99.8%) was purchased from Henan Bafusi Chemical Products Co., Ltd. Formaldehyde was purchased from Jinan Qicai Chemical Co., Ltd.
[0042] (2) Preparing a modifier, the preparation method thereof is as follows:
[0043] A1. Dissolve 10g of melamine modified resin in 110mL of ethanol solution to obtain a resin solution. The mass fraction of the ethanol solution is 40%. The specific dissolution process is stirring at a constant speed of 250r / min for 15min.
[0044] A2. Add 4.5g of boric acid to the resin solution obtained in A1, heat and stir to dissolve. The specific operation is to heat to 48°C, stir at a speed of 160r / min, and stir for 38min to obtain the modifier. Heating can accelerate the reaction rate, while stirring helps to maintain the uniform distribution of the reactants and prevent local overheating or precipitation. Under heating conditions, boric acid reacts with the hydroxyl groups in the resin, releasing water molecules while introducing boron elements into the resin, and can form a more stable three-dimensional network structure, so as to achieve a better structural modification effect in subsequent use.
[0045] Among them, boric acid (capacitor grade) is purchased from Qinghai Liada Chemical Co., Ltd.
[0046] (3) A method for preparing a zinc-bromine flow battery electrode material, comprising the following steps:
[0047] S1. Cut the beech wood into slices with a thickness of 5 mm along the vertical growth direction, first use water ultrasonic cleaning for 6 hours, then use ethanol ultrasonic cleaning for 6 hours, and then dry it at a drying temperature of 60°C and a drying time of 13 hours to obtain clean wood chips.
[0048] S2. Immerse the clean wood chips obtained in S1 in a modifier, the amount of which is 5 times the mass of the clean wood chips. Heat to 42°C to promote the modifier to adhere to the surface of the wood chips and penetrate into the interior of the wood chips. After keeping warm for 11 hours, take out and dry them at 60°C for 8 hours to obtain modified wood chips.
[0049] S3. The modified wood chips obtained in S2 are calcined in an argon atmosphere at 360° C. for 1 h, then at 960° C. for 2 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0050] The zinc-bromine flow battery electrode material was characterized, and its morphology is shown in the figure Figure 3 and Figure 4 As shown, there are a large number of vertically oriented through holes distributed on the surface, with pore diameters ranging from 0.5 nm to 50 μm.
[0051] Example 2: The difference between this example and Example 1 is that: (3) A method for preparing a zinc-bromine flow battery electrode material comprises the following steps:
[0052] S1. Cut the beech wood into slices with a thickness of 6 mm along the vertical growth direction, first use water ultrasonic cleaning for 7 hours, then use ethanol ultrasonic cleaning for 7 hours, and then dry it at a temperature of 60°C for 14 hours to obtain clean wood chips.
[0053] S2. Immerse the clean wood chips obtained in S1 in the modifier, heat it to 45°C to promote the modifier to adhere to the surface of the wood chips and penetrate into the interior of the wood chips. After keeping warm for 10 hours, take it out and dry it at 70°C for 7 hours to obtain modified wood chips.
[0054] S3. The modified wood chips obtained in S2 are calcined in an argon atmosphere at 380° C. for 1 h, then at 980° C. for 2 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0055] Example 3: The difference between this example and Example 1 is that: (3) A method for preparing a zinc-bromine flow battery electrode material comprises the following steps:
[0056] S1. Cut the beech wood into slices with a thickness of 7 mm along the vertical growth direction, first use water ultrasonic cleaning for 8 hours, then use ethanol ultrasonic cleaning for 8 hours, and then dry it at a drying temperature of 70°C and a drying time of 15 hours to obtain clean wood chips.
[0057] S2. Immerse the clean wood chips obtained in S1 in the modifier, heat it to 45°C to promote the modifier to adhere to the surface of the wood chips and penetrate into the interior of the wood chips. After keeping warm for 12 hours, take it out and dry it at 70°C for 10 hours to obtain modified wood chips.
[0058] S3. The modified wood chips obtained in S2 are calcined in an argon atmosphere at 400° C. for 1 h, then at 1000° C. for 2 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0059] Example 4: The difference between this example and Example 1 is that: (3) A method for preparing a zinc-bromine flow battery electrode material comprises the following steps:
[0060] S1. Cut the beech wood into slices with a thickness of 6 mm along the vertical growth direction, first use water ultrasonic cleaning for 7 hours, then use ethanol ultrasonic cleaning for 7 hours, and then dry it at a temperature of 60°C for 12 hours to obtain clean wood chips.
[0061] S2. Immerse the clean wood chips obtained in S1 in the modifier, heat it to 40°C to promote the modifier to adhere to the surface of the wood chips and penetrate into the interior of the wood chips. After keeping warm for 10 hours, take it out and dry it at a drying temperature of 50°C for 7 hours to obtain modified wood chips.
[0062] S3. The modified wood chips obtained in S2 are calcined in an argon atmosphere at 360° C. for 2 h, then at 960° C. for 3 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0063] Comparative Example 1: The difference between this comparative example and Example 1 is that in the preparation of the zinc-bromine liquid flow battery electrode material, the modifier is deleted, and the two-stage calcination temperatures are 300° C. and 900° C. respectively.
[0064] Specifically, (3) a method for preparing an electrode material for a zinc-bromine flow battery comprises the following steps:
[0065] S1. Cut the beech wood into slices with a thickness of 5 mm along the vertical growth direction, first use water ultrasonic cleaning for 6 hours, then use ethanol ultrasonic cleaning for 6 hours, and then dry it at a drying temperature of 60°C and a drying time of 13 hours to obtain clean wood chips.
[0066] S2. The clean wood chips obtained in S1 are calcined in an argon atmosphere at 300° C. for 1 h, then at 900° C. for 2 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0067] Comparative Example 2: The difference between this comparative example and Example 1 is that the modifier is deleted in the preparation of the zinc-bromine liquid flow battery electrode material.
[0068] Specifically, (3) a method for preparing an electrode material for a zinc-bromine flow battery comprises the following steps:
[0069] S1. Cut the beech wood into slices with a thickness of 5 mm along the vertical growth direction, first use water ultrasonic cleaning for 6 hours, then use ethanol ultrasonic cleaning for 6 hours, and then dry it at a drying temperature of 60°C and a drying time of 13 hours to obtain clean wood chips.
[0070] S2. The clean wood chips obtained in S1 are calcined in an argon atmosphere at 360° C. for 1 h, then at 960° C. for 2 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0071] Comparative Example 3: The difference between this comparative example and Example 1 is that in the preparation of the zinc-bromine liquid flow battery electrode material, the two-stage calcination temperatures are 300° C. and 900° C. respectively.
[0072] Specifically, (3) a method for preparing an electrode material for a zinc-bromine flow battery comprises the following steps:
[0073] S1. Cut the beech wood into slices with a thickness of 5 mm along the vertical growth direction, first use water ultrasonic cleaning for 6 hours, then use ethanol ultrasonic cleaning for 6 hours, and then dry it at a drying temperature of 60°C and a drying time of 13 hours to obtain clean wood chips.
[0074] S2. Immerse the clean wood chips obtained in S1 in a modifier, the amount of which is 5 times the mass of the clean wood chips. Heat to 42°C to promote the modifier to adhere to the surface of the wood chips and penetrate into the interior of the wood chips. After keeping warm for 11 hours, take out and dry them at 60°C for 8 hours to obtain modified wood chips.
[0075] S3. The modified wood chips obtained in S2 are calcined in an argon atmosphere at 300° C. for 1 h, then at 900° C. for 2 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0076] Comparative Example 4: The difference between this comparative example and Example 1 is that a commercial carbon felt material with a thickness of 5 mm is cut into pieces with an area of 9 cm 2 , and then dried at 60 °C for 12 h and used directly as an electrode.
[0077] The commercial carbon felt electrode was characterized and its morphology was as follows Figure 5 As shown, the carbon fibers are interwoven and the pores are random and non-oriented.
[0078] Comparative Example 5: The difference between this comparative example and Example 1 is that in the preparation of the zinc-bromine liquid flow battery electrode material, beech wood is replaced by pine wood.
[0079] Specifically, (3) a method for preparing an electrode material for a zinc-bromine flow battery comprises the following steps:
[0080] S1. Cut the pine wood into pieces with a thickness of 5 mm along the vertical growth direction, first use water ultrasonic cleaning for 6 hours, then use ethanol ultrasonic cleaning for 6 hours, and then dry it at a drying temperature of 60°C and a drying time of 13 hours to obtain clean wood chips.
[0081] S2. Immerse the clean wood chips obtained in S1 in a modifier, the amount of which is 5 times the mass of the clean wood chips. Heat to 42°C to promote the modifier to adhere to the surface of the wood chips and penetrate into the interior of the wood chips. After keeping warm for 11 hours, take out and dry them at 60°C for 8 hours to obtain modified wood chips.
[0082] S3. The modified wood chips obtained in S2 are calcined in an argon atmosphere at 360° C. for 1 h, then at 960° C. for 2 h, and then cooled to room temperature to obtain a zinc-bromine liquid flow battery electrode material.
[0083] Test Example 1: Test objects: Electrodes were prepared according to Examples 1 to 4 and Comparative Examples 1 to 5.
[0084] Test items and methods: Each test object was applied to the zinc-bromine flow battery to test the efficiency performance. The test conditions were: the electrolyte composition was 2.5 mol / L zinc bromide + 3 mol / L potassium chloride + 0.8 mol / L 1-methyl-1-ethylpyrrolidine bromide, the diaphragm was a microporous polyolefin diaphragm, and the charge and discharge current densities were 20 mA / cm 2 , the charging SOC is 50%, and the discharge cut-off voltage is 0.6 V. The performance test data of the battery average coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE) are shown in Table 1.
[0085] Among them, the average coulomb efficiency (CE) = (the amount of charge released during discharge / the amount of charge input during charging) × 100%. It is an important indicator to measure the efficiency of charge transfer during battery charging and discharging, and directly reflects the energy loss and side reaction degree of the battery during the charge and discharge cycle. High coulomb efficiency means that the battery has less charge loss during charging and discharging, and the battery efficiency is higher.
[0086] Voltage efficiency (VE) = (operating voltage of the battery during discharge / theoretical voltage) × 100%. It reflects the voltage maintenance capability of the battery in actual use, that is, the degree to which the battery voltage decreases during discharge. High voltage efficiency means that the battery voltage drops less during discharge and the battery performance is better.
[0087] Energy efficiency (EE) = (released energy / stored energy) × 100%. It describes the number of transmission bits that can be obtained when the system consumes unit energy, and represents the efficiency of the system's use of energy resources. The higher the EE, the more transmission bits the system obtains when it consumes unit energy, which means that the system has a higher efficiency in using energy resources. For batteries, EE reflects the energy conversion efficiency of the battery in actual use.
[0088] Table 1. Test data of Experimental Example 1
[0089]
[0090] Result analysis: Analyze Example 1-Example 4 and combine the data in Table 1 and Figure 1It can be seen that the electrode material prepared by the present invention is applied to zinc-bromine liquid flow batteries, and the average coulombic efficiency (CE) of the battery is as high as 94.7% or more, which means that during the charge and discharge process of the battery, more than 94.7% of the electricity can be effectively utilized and stored back. This is a very high ratio, indicating that the battery loses very little electricity during the cycle, thereby ensuring the long life and high stability of the battery. The voltage efficiency (VE) is as high as 84.1% or more. This high voltage efficiency means that the voltage change of the battery is small during the charge and discharge process, which helps to reduce the energy loss caused by voltage fluctuations during the use of the battery. The energy efficiency (EE) is as high as 79.7% or more. This high energy efficiency means that the battery can more effectively convert electrical energy into chemical energy and store it, and at the same time, it can efficiently convert chemical energy into electrical energy for external devices during discharge. In summary, it is shown that the electrode material prepared by the present invention has excellent electrochemical activity, can achieve efficient energy conversion and storage in the battery, and can ensure the excellent overall performance of the prepared battery.
[0091] Analyze Example 1 and Comparative Examples 1-3 and combine the data in Table 1 and Figure 1 By comparing Comparative Example 1 and Comparative Example 2, it can be seen that when no modifier is used for immersion, the temperature of the two calcinations is increased from 300°C and 900°C to 360°C and 960°C, which will cause the calcination temperature to be too high, resulting in a decrease in the electrochemical activity of the obtained electrode material, and ultimately resulting in a decrease in the overall performance of the obtained battery.
[0092] This is because natural wood has a directional hierarchical through-pore structure, which facilitates the penetration of electrolytes and the transport of ions; however, excessively high calcination temperatures (360°C and 960°C) can destroy or change these pore structures, thereby reducing the permeability of the electrolyte and the efficiency of ion transport. In addition, as the calcination temperature increases, the organic components in the wood will decompose more easily, which may also lead to a decrease in the mechanical strength of the electrode material, thereby affecting its stability and durability in the battery. In addition, excessively high calcination temperatures may also change the chemical properties of the wood surface, making it more likely to react with the electrolyte or other battery components, thereby affecting the performance and life of the battery.
[0093] By comparing Comparative Example 1 and Comparative Example 3, it can be seen that when the temperatures of the two calcinations are 300° C. and 900° C., soaking the electrode material with the modifier prepared by the present invention before calcination can improve the electrochemical activity of the electrode material, thereby improving the overall performance of the final battery.
[0094] By comparing Comparative Example 2 with Example 1, it can be seen that when the temperatures of the two calcinations are 360°C and 960°C, soaking the modified agent prepared by the present invention before calcination can also improve the electrochemical activity of the prepared electrode material, thereby improving the overall performance of the final battery.
[0095] Combined with the comparison between Comparative Example 3 and Example 1, it can be seen that when the temperatures of the two calcinations are 360°C and 960°C, the electrochemical activity of the electrode material is significantly improved by soaking in the modifier prepared by the present invention before calcination, which is significantly greater than when the temperatures of the two calcinations are 300°C and 900°C. Finally, in Example 1 and Comparative Examples 1 to Comparative Examples 3, the electrochemical activity of the electrode material prepared by Example 1 is the best when the temperatures of the two calcinations are 360°C and 960°C, and the modifier prepared by the present invention is soaked before calcination, and the overall performance of the battery prepared is the best.
[0096] Analyze Example 1 and Comparative Example 4 and combine the data in Table 1 and Figure 1 It can be seen that the electrochemical activity of the electrode material prepared by the present invention is better than that of the existing carbon felt electrode material.
[0097] Analyze Example 1 and Comparative Example 5 and combine the data in Table 1 and Figure 1 It can be seen that replacing the raw material beech wood for preparing the electrode material of the present invention with pine wood will lead to a decrease in the electrochemical activity of the prepared electrode material.
[0098] Test Example 2: Test objects: Electrodes were prepared according to Examples 1 to 4 and Comparative Examples 1 to 5.
[0099] Test items and methods: Each test object was applied to a zinc-bromine flow battery to test the performance improvement on reaction kinetics. The test conditions were: the electrolyte composition was 2.5 mol / L zinc bromide + 3 mol / L potassium chloride + 0.8 mol / L methylpyrrolidine, the diaphragm was a microporous polyolefin diaphragm, and the charge and discharge current densities were 10, 20, 30, 40, 50, and 60 mA / cm 2 , the charge capacity is 50% SOC, and the discharge cut-off voltage is 0.6 V. The performance data of the battery charge and discharge voltage difference (ΔV) at different current densities are shown in Table 2.
[0100] The battery charge and discharge voltage difference (ΔV) refers to the voltage difference between the two electrodes of the battery during charging or discharging. Reducing the voltage difference can improve the performance and life of the battery.
[0101] Table 2. Test data of Experimental Example 2
[0102]
[0103] Result analysis: Analyze Example 1-Example 4 and combine the data in Table 2 and Figure 2 It can be seen that when the electrode material prepared by the present invention is used in zinc-bromine liquid flow batteries, the battery charge and discharge voltage difference (ΔV) is small, indicating that the electrode material prepared by the present invention has excellent electrochemical activity.
[0104] Analyze Example 1 and Comparative Examples 1-3 and combine the data in Table 2 and Figure 2 By comparing Comparative Example 1 and Comparative Example 2, it can be seen that when no modifier is used for immersion, the temperature of the two calcinations is increased from 300°C and 900°C to 360°C and 960°C, which will cause the electrochemical activity of the obtained electrode material to decrease, and ultimately lead to an increase in the battery charge and discharge voltage difference (ΔV) of the obtained battery.
[0105] By comparing Comparative Example 1 and Comparative Example 3, it can be seen that when the temperatures of the two calcinations are 300°C and 900°C, soaking the electrode material with the modifier prepared by the present invention before calcination can improve the electrochemical activity of the prepared electrode material, thereby reducing the battery charge and discharge voltage difference (ΔV) of the prepared battery.
[0106] By comparing Comparative Example 2 with Example 1, it can be seen that when the temperatures of the two calcinations are 360°C and 960°C, soaking the electrode material with the modifier prepared by the present invention before calcination can also improve the electrochemical activity of the prepared electrode material, thereby reducing the battery charge and discharge voltage difference (ΔV) of the prepared battery.
[0107] Combined with the comparison between Comparative Example 3 and Example 1, it can be seen that when the temperatures of the two calcinations are 360°C and 960°C, the electrochemical activity of the electrode material is significantly improved by soaking in the modifier prepared by the present invention before calcination, which is significantly greater than when the temperatures of the two calcinations are 300°C and 900°C. Finally, in Example 1 and Comparative Examples 1 to Comparative Examples 3, the electrochemical activity of the electrode material prepared by Example 1 is the best when the temperatures of the two calcinations are 360°C and 960°C, and the modifier prepared by the present invention is soaked before calcination, and the battery charge and discharge voltage difference (ΔV) of the battery finally prepared is the lowest.
[0108] Analyze Example 1 and Comparative Example 4 and combine the data in Table 2 and Figure 2 It can be seen that the electrochemical activity of the electrode material prepared by the present invention is better than that of the existing carbon felt electrode material.
[0109] Analyze Example 1 and Comparative Example 5 and combine the data in Table 2 and Figure 2 It can be seen that replacing the raw material beech wood for preparing the electrode material of the present invention with pine wood will lead to a decrease in the electrochemical activity of the prepared electrode material, resulting in an increase in the battery charge and discharge voltage difference (ΔV) of the final battery.
[0110] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0111] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing an electrode material for a zinc-bromine flow battery, characterized in that: The steps include: S1, cutting the natural wood into pieces with a thickness of 5-7 mm along the vertical growth direction, and then ultrasonically cleaning and drying with deionized water and ethanol to obtain clean wood chips; the natural wood is beech; S2, immersing the clean wood chips obtained in S1 in a modifier, heating to 40-45°C, keeping warm for 10-12 hours, taking out, and drying to obtain modified wood chips; the modifier is an ethanol solution containing melamine modified resin and boric acid; S3, calcining the modified wood chips obtained in S2 at 360-400° C. for 0.5-2 h in an argon atmosphere, then calcining at 960-1000° C. for 2-3 h, and then cooling to room temperature to obtain a zinc-bromine liquid flow battery electrode material; The preparation method of the modifier is as follows: A1. Dissolve 10 g of melamine-modified resin in 100-120 mL of ethanol solution to obtain a resin solution; A2, add 4-5g of boric acid to the resin solution obtained in A1, heat and stir to dissolve, and obtain the modifier; The preparation method of the melamine modified resin is as follows: B1. Add 94.11 g of phenol and 33.3 g of 30% NaOH solution into a four-necked flask, and stir at room temperature for 10 min. B2, then add 60.06g of formaldehyde, react at 45℃ for 20min, slowly raise the temperature to 85℃, keep warm and continue to react for 30min; B3. Then add 50.4-62.6g of melamine and 24-32g of formaldehyde, evenly raise the temperature to 90°C, keep warm for 2-3h, and finally cool to 45°C to obtain melamine-modified resin.
2. The method for preparing the zinc-bromine flow battery electrode material according to claim 1, characterized in that: In A1, the mass fraction of the ethanol solution is 35-45%.
3. The method for preparing the zinc-bromine flow battery electrode material according to claim 1, characterized in that: In A2, the specific operation of heating and stirring to dissolve is: heating to 45-50°C, stirring speed 150-180r / min, stirring time 35-40min.
4. The method for preparing the zinc-bromine flow battery electrode material according to claim 1, characterized in that: In S1, ultrasonic cleaning is performed with water for 6-8 h, and then ultrasonic cleaning is performed with ethanol for 6-8 h.
5. The method for preparing the zinc-bromine flow battery electrode material according to claim 1, characterized in that: In S1, the drying temperature is 50-70°C and the drying time is 12-15h.
6. The method for preparing the zinc-bromine flow battery electrode material according to claim 1, characterized in that: In S2, the drying temperature is 50-70°C and the drying time is 7-10h.
7. A zinc-bromine flow battery electrode material, characterized in that: The method is prepared according to any one of claims 1 to 6.
Citation Information
Patent Citations
Manufacturing method of nitrogenous carbon electrode and flow cell provided therewith
US20170222230A1